2001
DOI: 10.1889/1.1831884
|View full text |Cite
|
Sign up to set email alerts
|

25.1: Improvement on Longevity of Blue Phosphor for PDP Applications

Abstract: Improvement in longevity of blue phosphor (Eu 2+ -activated barium magnesium aluminate, call as BAM) is investigated for the application of color plasma displays. It is clarified that the properties of phosphor deterioration caused by the irradiation of vacuum ultraviolet rays are dependent on the substituted elements for the specific part of the BAM. The longevity of the modified BAM is longer than that of the conventional one by twice or more by means of the substitution of In, Lu or Sc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The blue phosphor, BaMgAl 10 O 17 :Eu 2+ (BAM), has been of particular interest because it is considerably less stable than the red and green emitters, both during panel fabrication (thermal damage) and panel operation (VUV damage). These phenomena have been documented in numerous publications. While the thermal damage in these materials has been reasonably assigned to the oxidation of Eu 2+ to Eu 3+ , the mechanisms of VUV damage have remained somewhat more mysterious. Part of the difficulty is that many of the VUV damage studies have been conducted using functioning panels, or through long exposures to VUV radiation from discharge tubes that do not reproduce the magnitude of the photon fluxes seen in displays.…”
Section: Introductionmentioning
confidence: 96%
“…The blue phosphor, BaMgAl 10 O 17 :Eu 2+ (BAM), has been of particular interest because it is considerably less stable than the red and green emitters, both during panel fabrication (thermal damage) and panel operation (VUV damage). These phenomena have been documented in numerous publications. While the thermal damage in these materials has been reasonably assigned to the oxidation of Eu 2+ to Eu 3+ , the mechanisms of VUV damage have remained somewhat more mysterious. Part of the difficulty is that many of the VUV damage studies have been conducted using functioning panels, or through long exposures to VUV radiation from discharge tubes that do not reproduce the magnitude of the photon fluxes seen in displays.…”
Section: Introductionmentioning
confidence: 96%
“…VUV damage may result from a radiation-induced change in the oxidation state of Eu, from migration of ions in the Ba-O plane of the host, or from the formation of some other electronic defects. Many methods have been proposed for improving the stability of BAM, ranging from modest compositional variations [5][6][7] to the introduction of trivalent ions into the host lattice [8,9]. However, none of these approaches has led to dramatic improvements in the stability of the phosphor, and many questions remain about the fundamental nature of these degradation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…One is to adopt BAM solid solution with Ba-poor aluminate for improving thermal degradation [10][11] . The other is to add elements such as rare earth into BAM for reducing the damage caused by VUV-irradiation [12] . In addition, it is also found that the BAM degradation properties are influenced by aluminum concentration in (Ba 0.9 , Eu 0.1 )MgAl x O 2+1.5x (x=7-16) as shown in Figure 6, and the detailed results are summarized in reference [24] .…”
Section: Improvements Of Blue Phosphors 41 Improvements Of Bam Degramentioning
confidence: 99%
“…The most serious problem is the degradation of blue phosphor during the panel processing and operation which results in a loss of efficiency and color purity [2][3][4][5] . In order to solve these problems, the degradation mechanisms on BAM are being studied actively [2][3][4][5][6][7][8][9][10][11] , and several improvements for BAM degradation are proposed [10][11][12][13][14] . On the other hand, new blue phosphors that have high emission efficiency under vacuum ultraviolet (VUV) excitation are being searched for PDP application [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%